Understanding and Engineering the Stereoselectivity of Humulene Synthase. Issue 37 (11th August 2021) - Schotte, Carsten; Lukat, Peer; Deuschmann, Adrian; Blankenfeldt, Wulf; Cox, Russell J.
Abstract: The non‐canonical terpene cyclase AsR6 is responsible for the formation of 2 E, 6 E, 9 E ‐humulene during the biosynthesis of the tropolone sesquiterpenoid (TS) xenovulene A. The structures of unliganded AsR6 and of AsR6 in complex with an in crystallo cyclized reaction product and thiolodiphosphate reveal a new farnesyl diphosphate binding motif that comprises a unique binuclear Mg 2+ ‐cluster and an essential K289 residue that is conserved in all humulene synthases involved in TS formation. Structure‐based site‐directed mutagenesis of AsR6 and its homologue EupR3 identify a single residue, L285/M261, that controls the production of either 2 E, 6 E, 9 E ‐ or 2 Z, 6 E, 9 E ‐humulene. A possible mechanism for the observed stereoselectivity was investigated using different isoprenoid precursors and results demonstrate that M261 has gatekeeping control over product formation. Abstract : AsR6 is a type I sesquiterpene cyclase with very low homology to other terpene cyclases. It has a unique bi‐magnesium diphosphate binding site and thus lacks the canonical terpene cyclase aspartate‐rich signature sequences. One magnesium is replaced by the ϵ‐ammonium ion of a conserved lysine. AsR6 can use FPP and both enantiomers of NPP as substrate. In addition, a single mutation directs formation of 2 E or 2 Z humulene with very high selectivity.